1999
DOI: 10.1590/s0034-71081999000100018
|View full text |Cite
|
Sign up to set email alerts
|

Desmídias de ambientes fitotélmicos bromelícolas

Abstract: Desmids of phytothelmic environmentsWater is accumulated in phytotelmata (plant pond) of Bromeliads and usually favor algal development. Twenty-five samples were taken in these environments placed on coastal and mountain regions of Rio de Janeiro State, Brasil. Desmids were dominant in nineteen of these samples. Ten species, three varieties and one taxonomic form were identified. In addition, representatives of Chlorophyceae, Cyanophyceae, Bacillariophyceae, Xanthophyceae and Dinophyceae were found.Key words: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
1
13
1
5
Order By: Relevance
“…Brasil: Rio de Janeiro (Sophia 1999), Rio Grande do Sul ). Segundo Prescott et al (1981), C. botrytis é extremamente variável em forma da semicélula e na disposição dos grânulos.…”
Section: Figuras 8-10unclassified
See 2 more Smart Citations
“…Brasil: Rio de Janeiro (Sophia 1999), Rio Grande do Sul ). Segundo Prescott et al (1981), C. botrytis é extremamente variável em forma da semicélula e na disposição dos grânulos.…”
Section: Figuras 8-10unclassified
“…Distribuição geográfica: Brasil: Goiás (Förster 1964), Rio de Janeiro (Sophia 1999), Distrito Federal, Lagoa Bonita, (Leite 1990 Células grandes, tão longas quanto largas; constrição mediana profunda, seno aberto, margem basal côncava; semicélulas elipsóides, margem lateral com oito espinhos pontiagudos grandes (até 13 µm) e vários pequenos, presença de verrugas na parede celular; cloroplasto axial, com dois pirenóides por semicélula; vista apical elíptica com três espinhos visíveis em cada uma das duas extremidades da semicélula. Compr.…”
Section: Cosmarium Contractumunclassified
See 1 more Smart Citation
“…Tank bromeliads form an "oasis" within the semi-arid area, as these plants usually are the only source of water available to many organisms that live nearby (Islair et al 2015). Most studies in these environments are targeted to the fauna, especially invertebrates, and little is known about algal diversity in these microcosms (Sophia 1999). The relationship between bromeliads and algae is still a largely unexplored and poorly understood topic (Marino et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bromeliads in neotropical forests serve as habitats for bacteria (Haubrich et al 2009), algae (Brouard et al 2011), fungi (Sophia 1999), protozoa (Foissner et al 2003), arthropods and anuran amphibians (Benzing 1990, Silva et al 2011. Some invertebrates, such as oligochaetes and ostracods, spend their entire lives inside the cisterns of bromeliads (Montero et al 2010, Pinto & Jocqué 2013, while others are only found in such habitats in immature forms, mainly beetles and flies (Mestre et al 2001).…”
Section: Introductionmentioning
confidence: 99%